2005
DOI: 10.3750/aip2005.35.2.09
|View full text |Cite
|
Sign up to set email alerts
|

The effect of MS-222 on the cardiac and respiratory function and behaviour of common carp, Cyprinus carpio L., during general anaesthesia

Abstract: Dziaman R., K∏yszejko B., Hajek G. 2005. The effect of MS-222 on the cardiac and respiratory function and behaviour of common carp, Cyprinus carpio L., during general anaesthesia. Acta Ichthyol. Piscat. 35 (2): 125-131.Background. Assessments of the efficacy of anaesthetics are usually based on observations of fish behaviour or changes in blood parameters. In this study we attempted to assess the process of anaesthesia, caused by MS-222, based on the measurement of heartbeat and respiratory frequency. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The presence of outliers could be partly due to the negative correlation between OpR and time under anaesthesia (fish were exposed to different concentrations in a randomized order); however, this correlation was not as strong as the correlation to anaesthetic concentration. Similar decrease in OpR has been previously described in carp in correlation with anaesthetic concentration (Dziaman 2005).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The presence of outliers could be partly due to the negative correlation between OpR and time under anaesthesia (fish were exposed to different concentrations in a randomized order); however, this correlation was not as strong as the correlation to anaesthetic concentration. Similar decrease in OpR has been previously described in carp in correlation with anaesthetic concentration (Dziaman 2005).…”
Section: Discussionsupporting
confidence: 88%
“…The difference in results may be explained by the difference in water delivery systems used in both studies, since we have used a water pump to create a ‘flow–through’ system which does not rely on active opercular movements to provide oxygenated water to the gills. Blood gas parameters were not recorded in the study by Dziaman (2005) and so cannot be compared to our results, although changes in respiratory rate, that were recorded in the study, could have potentially led to moderate hypoxia which has been shown to lead to physiological tachycardia in carp (Glass et al. 1991).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Cortisol values measured 1 h following anesthesia study, may not reflect the maximum magnitude of stress response in this study, as time‐series sampling was not done (McDonald and Milligan, 1992; Hrubec and Smith, 2000). Acute reddening of the skin was associated with elevated cortisol levels in this study and may indicate changes in blood circulation resulting from hyperactivity or from tissue hypoxia following marked decreases in ventilation rate (Sladky et al., 2001; Dziaman et al., 2005).…”
Section: Discussionmentioning
confidence: 51%
“…Overdose of an anaesthetic or retaining the fish in an anaesthetic bath for too long leads to the fading of ventilation, hypoxia, and finally, respiratory and cardiac collapse (Tytler & Hawkins 1981). The fading of ventilation is an important warning sign suggesting that the exposure should be terminated (Hajek & Klyszejko 2004;Dziaman et al 2005).…”
mentioning
confidence: 99%